Pengaruh Satisfaction with Interinsic Reward (SIR), Work Life Balance, & Satisfaction with Exterinsic Reward (SER) terhadap Job Satisfaction yang Mempengaruhi Turnover Intention Industri Perhotelan Jakarta - Tri Adiyono, Yunia; Gunawan P, Andreas Wahyu; Justine Tanuwijaya (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Turn over intention has been seen as a crucial issue for company management for many years because it has negative impacts on organizations such as the loss of employee expertise, experience and skills. The method used is descriptive quantitative method by distributing questionnaires to hotel employees in Jakarta. With the aim of conducting empirical testing of all hypothesis formulations in research by means of hypothesis testing. The results obtained are from the analysis of the effect of the hypothesis of satisfaction with intrinsic reward (SIR) which has a significant positive effect on job satisfaction; Worklife balance (WLB) has a positive but not significant effect on job satisfaction; satisfaction with extrinsic reward (SER) has a significant positive effect on job satisfaction; and Job satisfaction has a significant positive effect on turnover intention.